Effects of dark chocolate consumption on the prothrombotic response to acute psychosocial stress in healthy men - Känel, Roland von; Meister, Rebecca E.; Stutz, Monika; Kummer, Petra; Arpagaus, Angela; Huber, Susanne; Ehlert, Ulrike; Wirtz, Petra H. (Thrombosis and Haemostasis, 2014)
Flavanoid-rich dark chocolate consumption benefits cardiovascular health, but underlying mechanisms are elusive. We investigated the acute effect of dark chocolate on the reactivity of prothrombotic measures to psychosocial stress. Healthy men aged 20–50 years (mean ± SD: 35.7 ± 8.8) were assigned to a single serving of either 50 g of flavonoid-rich dark chocolate (n=31) or 50 g of optically identical flavonoid-free placebo chocolate (n=34). Two hours after chocolate consumption, both groups underwent an acute standardised psychosocial stress task combining public speaking and mental arithmetic. We determined plasma levels of four stress-responsive prothrombotic measures (i. e., fibrinogen, clotting factor VIII activity, von Willebrand Factor antigen, fibrin D-dimer) prior to chocolate consumption, immediately before and after stress, and at 10 minutes and 20 minutes after stress cessation. We also measured the flavonoid epicatechin, and the catecholamines epinephrine and norepinephrine in plasma. The dark chocolate group showed a significantly attenuated stress reactivity of the hypercoagulability marker D-dimer (F=3.87, p=0.017) relative to the placebo chocolate group. Moreover, the blunted D-dimer stress reactivity related to higher plasma levels of the flavonoid epicatechin assessed before stress (F=3.32, p = 0.031) but not to stress-induced changes in catecholamines (p’s=0.35). There were no significant group differences in the other coagulation measures (p’s≥0.87). Adjustments for covariates did not alter these findings. In conclusion, our findings indicate that a single consumption of flavonoid- rich dark chocolate blunted the acute prothrombotic response to psychosocial stress, thereby perhaps mitigating the risk of acute coronary syndromes triggered by emotional stress.
Keywords: Blood coagulation; cardiovascular disease; catecholamines; epicatechin; psychological stress